Evaluating of Islamic Education: Literature Review - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
The evaluation of Islamic education is included in this paper. The goal of the study was to link Islamic education (990 papers) and non-formal education (95 papers) from 1958 to 2022. The retrieved bibliographic citation information is examined using the VOSviewer tool. Authors, journals, keywords, and citation references with the highest productivity are evaluated. Calculations have been made to determine the proportional growth rate and the time needed to double. between 1958 and 2022. The study's findings revealed what needs to be done in order for evaluating of Islamic education to adapt to education 4.0 in order to reach society 5.0. Through bibliometric analysis, the research's uniqueness revealed the addition of new literature about nonformal education and Islamic education, and there was variation.